1969
DOI: 10.1039/tf9696500496
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of decomposition of sodium dithionite in aqueous solution

Abstract: The thermal decomposition of sodium dithionite in aqueous solution has been followed by means of e.p.r. signal intensity measurements. Two different reactions have been identified. The first one, catalyzed by bisulphite ion, proceeds according to the usual second-order autocatalytic reaction mechanism. The second one, much faster than the first one, appears after an induction period and ends as soon as a sufficient amount of decomposition product has been formed. Using previously reported values for the equili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
14
0

Year Published

1978
1978
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 0 publications
4
14
0
Order By: Relevance
“…The initial step is believed to be the homolytic dissociation followed by attack of the radical anion SO, on the dithionite ion or its protonated dcrivative; equations (17) and (18). Steudel [27] showed that the HS20,ion contains an OH group rather than an SH group like HS,O, [23, 241. During the initial stages of the dithionite decomposition the concentration of thiosulfatc is lower than expected on the basis of equation (2). This has also becn observed by other authors [7, 91 and is confirmed by our results.…”
Section: Iliscussionsupporting
confidence: 93%
“…The initial step is believed to be the homolytic dissociation followed by attack of the radical anion SO, on the dithionite ion or its protonated dcrivative; equations (17) and (18). Steudel [27] showed that the HS20,ion contains an OH group rather than an SH group like HS,O, [23, 241. During the initial stages of the dithionite decomposition the concentration of thiosulfatc is lower than expected on the basis of equation (2). This has also becn observed by other authors [7, 91 and is confirmed by our results.…”
Section: Iliscussionsupporting
confidence: 93%
“…The aqueous solution of sodium dithionite is unstable 29 Molybdenum Blue +2SO 2 (g) This redox process in fact causes the motion of the SOMs oxidizing the dithionite and reducing the SOMs. The propulsion of SOMs due to the oxidation of SO 2 is coupled with the reduction of SOMs and thus the emergence of Mo V  Mo VI intervalence charge transfer (IVCT) in the molybdenum blue SOMs; the extent of SO 2 evolution can hence be monitored by electronic absorption spectroscopy (Fig.2).…”
Section: Resultsmentioning
confidence: 99%
“…The location of the incorporated deuterium was confirmed to be the C5 of uracil by the following series of observations: (i) incubation of reduced enzyme with 5D-dUMP in H 2 O resulted in loss of the deuterium label (Figure S1b); (ii) tritium of [5- 3 H]-dUMP was released into water upon incubation with reduced FDTS (Figure S2e) but not with oxidized FDTS or without the enzyme; and (iii) in the same experiment with [6- 3 H]-dUMP, all of the tritium remained on dUMP (Figure S2b), indicating that the reduced enzyme catalyzes the exchange of the C5 hydrogen and not that of C6. The choice of the reducing agent (sodium dithionite vs NADPH) had no effect on the observed dUMP deuteration (Figure 3b,d), ruling against dithionite decomposition products (e.g., thiosulfate) 15 as uracil activators. The exchange on C5 of uracil generally requires Michael addition at C6 (Scheme S1), as demonstrated with a variety of nucleophiles in solution (see Supporting Information for references).…”
mentioning
confidence: 98%